A full‐domain fluidic‐thermal approach for a high‐speed PMSM considering the bearing components. Issue 2 (4th October 2021) - Zhu, Gaojia; Li, Longnv; Xue, Ming; Liu, Tao
Abstract: This paper presents a refined full‐domain model for the fluidic‐thermal coupled analyses of a 15‐kW 30, 000‐rpm high‐speed permanent magnet synchronous machine (HS‐PMSM) considering the heat generation and dissipation of the bearing components. In order to analyse the heat dissipation capacities of the bearing components, firstly, the fluid flow conditions inside the bearings with different revolution and rotation ratios are researched, and the most serious case is taken in the full‐domain calculations. Secondly, the three‐dimensional (3D) full‐domain model is established, and the fluidic‐thermal analyses are conducted based on the basic principles of numerical heat transfer and CFD. During calculations, in order to obtain the temperature rise precisely, the angular contact ball bearings are well modelled with all the internal components including the oil films, and the frictional loss in the bearings are computed by the Palmgren model. A 15‐kW 30, 000‐rpm HS‐PMSM prototype is established and tested to verify the full domain thermal modelling methodologies and indirectly validate the bearing performance calculations. Finally, a self‐ventilated structure is employed to prevent the bearing temperature rise, and the cooling effectiveness is validated by numerical calculations.